Methodology of research on nations and nationalism in modern Russian historiography (based on the concept of Russianness) - A.R. Gimatdinova; N.I. Nedashkovskaya (Ученые записки Казанского университета: Серия Гуманитарные науки)
The methodology for studying nations and nationalism in modern Russian historiography was analyzed. The concept of Russianness was considered, and, as a result, it was demonstrated that the scope of tools and methods used in intellectual history can be expanded. The scientific and research discourse of the notions of nation, nationalism, and, in particular, Russianness was outlined. The conceptualization of the latter – in the works by A.I. Miller, M.D. Dolbilov, and E.A. Vishlenkova – was considered. The limits of the concept were defined. Its place in the historiographical notions of nation and nationalism, identity and empire was revealed. The intentions of the authors of historiographic statements were identified based on the works published by the Cambridge School of Intellectual History. The biographical approach was used: the role played by personal views of a researcher, which inevitably humanize the history of historiography, was discussed. Special attention was paid to cognitive metaphors enabling both deconstruction of the meaning of statements and identification of the content of their internal structures, such as ideologemes or frames.